2020
DOI: 10.22541/au.159068332.24862763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matrix Metalloproteinase 3 as a Valuable Marker for Patients with COVID-19

Abstract: Background: The situation of the corona virus disease 2019(COVID-19) continues to evolve, our study explored the significance of serum levels of Matrix Metalloproteinase 3 (MMP3) as a marker for patients with COVID-19. Methods: Sixty-two COVID-19 patients in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Metallopeptidase activity (MMP group genes) affects respiratory disorders, including ARDS, acute lung injury, lung cancer, and pulmonary fibrosis. The significance of metalloproteinase as a biomarker for infected lung patients with COVID-19 was investigated in [ 49 , 50 ]. According to the cellular component, top GO terms are integral components of the luminal side of the endoplasmic reticulum membrane (six genes) and MHC protein complex (five genes).…”
Section: Discussionmentioning
confidence: 99%
“…Metallopeptidase activity (MMP group genes) affects respiratory disorders, including ARDS, acute lung injury, lung cancer, and pulmonary fibrosis. The significance of metalloproteinase as a biomarker for infected lung patients with COVID-19 was investigated in [ 49 , 50 ]. According to the cellular component, top GO terms are integral components of the luminal side of the endoplasmic reticulum membrane (six genes) and MHC protein complex (five genes).…”
Section: Discussionmentioning
confidence: 99%
“…The MMPs are a group of proteases directly associated with inflammatory cytokines/chemokines ( e.g. IL-6) [65] , [66] , [67] , [68] , [69] . Based on the assessments, the plasma level of MMP-9 in patients with COVID-19 has been higher than in the control group from the earliest days of hospitalization and has culminated along with the disease progress.…”
Section: Sars-cov-2 and Pro-inflammatory Pathwaysmentioning
confidence: 99%
“…Notably, this MMP can activate other members of the MMPs family ( e.g. MMP-9) resulting in the disease conditions exacerbation [66] , [67] . As pointed before, MMPs possess proteolytic activity.…”
Section: Sars-cov-2 and Pro-inflammatory Pathwaysmentioning
confidence: 99%
“…Released MMP-9 from inflammatory cells does promote alveolar capillary destruction leading to lung injury [83,84,87]. Also, Shi et al suggested that MMP-3 serum level may be a valuable marker of COVID-19 by indicating a significant difference found between novel coronavirus pneumonia-infected patients and healthy people [88]. This particular MMP is widely expressed in human tissues since it is capable of cleaving several components of ECM components.…”
Section: Mediators Of Lung Ecm Breakdownmentioning
confidence: 99%
“…In fact, basic TIMP-1 levels are in first place low but are highly induced after triggered immune response on the contrary of TIMP-2, TIMP-3 and TIMP-4 that are constitutively secreted and modifications in their levels are lower than those of TIMP-1 in immune response [105][106][107][108][109]. The increase of MMP-3 [88] and MMP-9 [85] circulating levels during first days of infection on the optimum of the viral charge and a probable downregulation of their specific inhibitors could put the puzzle in this way: the virus turns all of the mediators in its favor by enhancing MMPs secretion during first days of infection that triggers a matrix disequilibrium. Their decrease in the upcoming period suggests an upregulation of their specific inhibitors to respond their sudden elevation.…”
Section: Mediators Of Lung Ecm Breakdownmentioning
confidence: 99%